The Need to Reform the Political Role of the African Union in Promoting Democracy and Human Rights in Domestic States: Making States More Accountable and Less Able to Avoid Scrutiny at the United Nations and at the African Union, Using Swaziland to Spotlight the Issues. Issue 1 (February 2018) - Sarkin, Jeremy
Abstract : This article examines how effective the African Union (AU) has been in pushing states to be more democratic in nature and to respect, protect, fulfil and promote the human rights of their inhabitants. It reviews the political role of the AU in this regard using the situation in Swaziland to do so. The article also examines Swaziland at the United Nations' Universal Periodic Review (UPR) process as a comparative tool.